2015
DOI: 10.1007/s13187-015-0869-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Learning in Oncology of Undergraduate Nursing with the Use of Concept Mapping

Abstract: This study aims to identify whether the use of concept mapping (CM) strategy assists a student to extend and revise their expertise in oncology and analyze the abilities developed in a student in order to go through theoretical to practical knowledge. This study is descriptive and qualitative, with 20 undergraduate students of the Undergraduate Nursing Course of Paulista School of Nursing of Federal University of São Paulo, Brazil. The critical incident technique and content analysis were used. There were 12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…On agreement with the study done by Khajavi & Ketabi (2012) the results revealed that students which used concept mapping have greater achievement in their learning and perceived self-efficacy in comparison to students which used traditional method strategy .furthermore Sarhangi et al (2010) demonstrated that concept mapping improve perceptions about ideas or concepts of students, that enable them to understand their mistakes and encourage students to learn effectively. as well as Trevisani et al (2016) found that concept mapping increase students ability to think independently In the same line Hagell and colleagues (2016) stated that, transformation and application of theoretical learned knowledge to be experienced interactively, conceptual mapping provide chances for students to test their knowledge perfectlyThis was supported by Samawi, Z., Miller, T. and Haras, M. (2014)study stated that the concept maps complexity degree is increased with passing of time. It has been illustrated that concept mapping is maintain long-term learning, enable moving from theory to real clinical practice, and encourage students for being' self-confideny when handling care to patients.…”
Section: Discussionmentioning
confidence: 81%
“…On agreement with the study done by Khajavi & Ketabi (2012) the results revealed that students which used concept mapping have greater achievement in their learning and perceived self-efficacy in comparison to students which used traditional method strategy .furthermore Sarhangi et al (2010) demonstrated that concept mapping improve perceptions about ideas or concepts of students, that enable them to understand their mistakes and encourage students to learn effectively. as well as Trevisani et al (2016) found that concept mapping increase students ability to think independently In the same line Hagell and colleagues (2016) stated that, transformation and application of theoretical learned knowledge to be experienced interactively, conceptual mapping provide chances for students to test their knowledge perfectlyThis was supported by Samawi, Z., Miller, T. and Haras, M. (2014)study stated that the concept maps complexity degree is increased with passing of time. It has been illustrated that concept mapping is maintain long-term learning, enable moving from theory to real clinical practice, and encourage students for being' self-confideny when handling care to patients.…”
Section: Discussionmentioning
confidence: 81%
“…Twenty-four of the 41 retrieved papers were qualitative or quantitative research studies, eight described a model or tool used for data gathering in teaching or research, [35][36][37][38][39][40][41][42] and eight were personal reflections. [43][44][45][46][47][48][49][50][51] Most studies were carried out in the United Kingdom (n=12), 17,21,22,25,28,30,32,35,40,44,49,50 and the United States (n=8) 14,19,26,27,31,39,41,45 Others were from Australia, 46 Belgium, 18,24 Brazil, 33 Canada, 12,15,20,36,37 Cyprus, 43 Finland, 13 Ireland, 47,…”
Section: Paper Characteristicsmentioning
confidence: 99%
“…Thirty-two papers used CIT or reflection as learning tools in nursing and health professional education. [37][38][39][40][41][42]51 Tools included written critical incident reports, 13,16,17,21,22,28,31,33,40,51 semi-structured interviews, 5,18,19,[23][24][25][26]30,34 survey responses, 27 and reflective essays. 45 Some papers used multiple methods in collecting critical incidents: a reflective journal and focus group, 15 a critical incident questionnaire and group interview, 29 a combination of reflective journals, case studies, critical incident analyses, document analyses, and semi-structured interviews.…”
Section: Papers Using Critical Incidents or Reflection On Events As A Learning Toolmentioning
confidence: 99%
“…Although it is a method that has been started to be used since the early 1980s, it was first used in nursing education in 1992 (Daley, Morgan, & Beman, 2016). This technique is used in clinical applications, case presentations and lectures in nursing education (Bayindir et al, 2015;Khrais & Saleh, 2017;Trevisani et al, 2016;Uslu et al, 2013).…”
Section: Concept Mapmentioning
confidence: 99%